PENGARUH FAKTOR INDIVIDU, KETERIKATAN KARYAWAN, KOMITMEN ORGANISASIONAL, DAN NIAT UNTUK BERHENTI KARYAWAN BANK - Prihartanto Dwi Saputra; Tantri Yanuar Rahmat Syah (MANAJEMEN DEWANTARA, 2023)
This research aimed to analyze the influence of individual factors, employee engagement, organizational commitment, and turnover intention. The respondent for this research is a public bank employee in the Serang and Cilegon located in Banten Province. Data collection was done in December 2022. The study was designed to collect data using an online survey method by distributing questionnaires. The respondents for this study were selected using purposive sampling, with a total sample of 120 public bank employees in the marketing department, including both permanent and contract employees. This is a quantitative study using the PLS Structural Equation Model (SEM) method and the Smart PLS 3.0 and SPSS software. The findings of this research suggest that individual factors have a positive effect on employee engagement, employee engagement has a positive effect and significant on organizational commitment, individual factors have no effect on organizational commitment, organizational commitment has no effect on the turnover intention, and employee engagement has a significant and negative influence on the turnover intention.